Otras miradas y aproximaciones a nuestras ciudades y sus asentamientos informales - Baietto, Gianni (2015)
The city is an expression of the life that dwells and interacts in it. The latter economic models have translated in a territorial capitalization that has mutilated the vital network of the cities, in a conflictive succession of fragmentary microspaces that support exclusion, suspicion and fear of others. In this context, a large amount of marginalized informal settlements have emerged in the past decades, in which we have identify rich interactions and integrations of colective and social-spatial dinamics, that have been nevertheless denied or invisibilized by ‘formality’ and officiality. Our interest towards these phenomena seeks to reinforce an attitude of a more respectful meeting and legitimacy, experiencing different ways of assuming our role as observants and participants, and actively involving ourselves with these social corps, setting out joint strategies that can contribute to their better quality of life and promotion of urban connectivity in a more inclusive city.